Teal organizations in the eyes of generation Z: Implementation problems in Russia - E. A. Nechvoloda; J. V. Matveeva (Вестник университета, 2022)
Basic concepts related to analysis and evaluation of teal organizations are reviewed, and generation Z’s attitude to the teal organizations implementation in Russia. Article analyses the classification and basic principles of teal organizations. Regional and federal organizations were reviewed as examples for research implementation. Authors have interviewed Samara University students with their own developed form as part of the research. With the students’ answers, the youth’s attitude to implementation of teal organizations has been determined and classified. The research data could be used not only for the determination of teal organizations’ key qualities mostly valuable for generation Z, but for the determination of key qualities for competent organization of common-typed enterprises by entrepreneurs.